Multiple factorial analysis of growth performance, gut population, lipid profiles, immune responses, intestinal histomorphology, and relative organ weights of Cobb 500 broilers fed a diet supplemented with phage cocktail and probiotics - Mohd Asrore, Mohd Shaufi; Sieo, Chin Chin; Chong, Chun Wie; Tan, Geok Hun; Abdul Rahman, Omar; Ho, Yin Wan (Taylor and Francis, 2024)
Previous studies on probiotics in chickens have shown varying efficacy, and the use of phage as a supplement for improving chicken performance and health has gained interest. However, the combination of these supplements has not been thoroughly investigated. This study aimed to assess the effects of an Escherichia coli phage cocktail, both alone and in combination with probiotics, on specific gut populations, lipid profiles, heterophil-to-lymphocyte ratio, serum immunoglobulins, villus height to crypt depth ratio, and relative organ weights in chickens at day 21 and 35. The experiment followed a completely randomised design with factorial arrangements, consisting of three levels of phage cocktail dosage (0 g/kg, 1 g/kg, and 2 g/kg) and two levels of probiotics dosage (0 g/kg and 1 g/kg), with a total of 288 one-day-old male Cobb 500 broilers. Our study demonstrated that supplementing chicken diets with 1 g/kg phage cocktail and 1 g/kg probiotics resulted in significant (p < 0.05) improvements in growth performance and reduced Clostridium perfringens populations. It also reduced triglyceride levels and did not cause physiological stress, as indicated by the heterophil-to-lymphocyte ratio. Overall, this study provides important insights into the potential benefits of combining phages and probiotics in broiler chicken diets, which have not been extensively studied.